2016
DOI: 10.5395/rde.2016.41.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant therapy enhances pulpal healing in bleached teeth

Abstract: ObjectivesThe purpose of this study was to evaluate the histopathological effects of an antioxidant therapy on the pulp tissue of rat teeth exposed to a bleaching gel with 35% hydrogen peroxide.Materials and MethodsForty rats were subjected to oral ingestion by gavage of distilled water (DW) or ascorbic acid (AA) 90 min before the bleaching therapy. For the bleaching treatment, the agent was applied twice for 5 min each to buccal surfaces of the first right mandibular molars. Then, the animals were sacrificed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, a recent study revealed areas of necrosis after 6 h of application of bleaching gel (Lima et al 2016). Thus, it may be that the pulp tissue observed in the present study at 2 days is in the process of regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study revealed areas of necrosis after 6 h of application of bleaching gel (Lima et al 2016). Thus, it may be that the pulp tissue observed in the present study at 2 days is in the process of regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…HP reaches the pulp chamber via the dentinal tubules, decreases cell metabolism and viability [ 6 , 7 ] and induces vascular permeability changes [ 8 ], DNA modifications and pulpal necrosis [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response in pulp tissues was evaluated in 27 in vivo studies, primarily assessed based on the intensity of inflammatory infiltrate in different thirds of pulp tissue (Benetti et al., 2017; Benetti, Briso, et al., 2018; Benetti, Briso, Carminatti, et al., 2019; Benetti, Briso, de AraĂșjo Lopes, et al., 2019; Benetti, Gomes‐Filho, et al., 2018; Carminatti et al., 2020; Cintra et al., 2013; Cintra et al., 2017; Cintra, Benetti, Ferreira, Gomes‐Filho, et al., 2016; Costa et al., 2010; da Silva et al., 2020; Ferreira et al., 2018; Gallinari et al., 2019; Kina et al., 2010; Lima et al., 2016; Louzada et al., 2019; Robertson & Melfi, 1980; Roderjan et al., 2015; Silva‐Costa et al., 2018; Terayama et al., 2020; Vaz et al., 2016), or by counting inflammatory cells (Cintra, Benetti, Ferreira, Rahal, et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies (19 studies), 18 of them assessed the inflammatory response, and all demonstrated significant inflammation in the most superficial regions of coronal pulp, often accompanied by necrotic areas. This was particularly evident after bleaching with 35% or 38% HP and during the initial periods (Barbosa et al., 2019; Benetti et al., 2017; Benetti, Briso, et al., 2018; Benetti, Briso, Carminatti, et al., 2019; Benetti, Briso, de AraĂșjo Lopes, et al., 2019; Benetti, Gomes‐Filho, et al., 2018; Carminatti et al., 2020; Cintra et al., 2013, 2017; Cintra, Benetti, Ferreira, Gomes‐Filho, et al., 2016; da Silva et al., 2020; Ferreira et al., 2018; Gallinari et al., 2019; Lima et al., 2016; Louzada et al., 2019; Seale et al., 1981; Silva‐Costa et al., 2018; Terayama et al., 2020).…”
Section: Resultsmentioning
confidence: 99%